Peer-learning reviews to improve Gauteng community-oriented primary care: Findings from AitaHealth™-enabled ward-based outreach teams - Tessa S. Marcus; Elizabeth Reji; Sanele Ngcobo (AOSIS, 2020)
Background: In 2016 the Gauteng Department of Health engaged University of Pretoria Family Medicine to provide` education, training and information and communication technology support for the phased scale-up of ward-based outreach teams (WBOTs) through community-oriented primary care (ICT-enabled COPC). As in all service delivery, quality assurance is essential. In contemporary best practice, it brings together peer-to-peer learning and quality improvement (QI) in what is termed here as peer-learning reviews (PLRs). Aim: To assess implementation fidelity and assure the quality of community-based healthcare services. Setting: This study was conducted in two districts of Gauteng province, South Africa. Methods: A 3-day PLR of paired WBOTs was conducted by multi-disciplinary teams of academics, partners and site-selected healthcare practitioners. Guided by a benchmark survey distilled from the seven COPC practice elements, they conducted individual interviews, accompanied WBOT members in field and facilitated solution-focused peer exchange workshops with all participants. Results: At all sites there was clear evidence of achievements and practical challenges with respect to mapping; support, networks and partnerships; infrastructure and functional equipment; work integrated learning; data and service activities; and performance status and management. Methodologically, PLRs supported inclusive, context-specific learning for all along the healthcare service pathway. They generated action plans derived from shared understanding and joint decision-making. Conclusion: The PLRs and the implementation results demonstrate the importance of structuring learning into service and research. Both helped develop participants' abilities to understand what they do, do their work, grow their sense of self-worth and improve their relationship with others.